ANALYSIS OF TECHNOLOGY AND MEANS OF HORIZONTAL WELLS FOR THE EXTRACTION OF HARDLY RECOVERABLE AND DEPLETION OF OIL AND GAS RESERVES (Oil and Gas Engineering, 2017)
In a scientific paper analyzes the technologies and means of construction of inclined and horizontal wells. In scientific work the question of the relevance and effectiveness of the rotary steerable systems (RSS). A comparison of drilling using RSS compared with drilling the same interval downhole drilling motors. Conducted a broad analysis of experience with rotary steerable systems on different fields. The conclusion about the great prospects of this technology in spite of the high costs and minor problems in complicated geological conditions of drilling.Keywords: rotary steerable systems, downhole drilling motors, bent, horizontal completion, whipstock, power rotary steerable systems